Analisis Peran Ganda Perempuan Yang Bekerja Sebagai Buruh Bangunan di Kota Kendari - Laxmi Laxmi; La Ode Aris; Zainal Zainal; Erens E Koodoh (Education : Jurnal Sosial Humaniora dan Pendidikan, 2021)
The formulation of the problem in this research is how women act as construction workers in Kendari City and why these women choose to be construction workers as their job. This research was carried out with the aim of knowing, understanding and describing women's activities as construction workers and the reasons for choosing work as construction workers. The method used in this research is field research using open, unstructured interviews (semi-structured interviews) and observations, both casual observations and involved observations of the activities of five female construction workers in Kendari City, with purposive selection of informants. sampling which was analyzed descriptively qualitatively.The results of this research can be seen that women as construction workers before carrying out their activities outside the home as construction workers, first complete their domestic role as housewives, as well as when they return home even though they have spent approximately eight hours outside to carry out their work. public role as a construction worker to meet the family's needs, this woman still has to carry out her duties as a housewife. This fact also illustrates that women who work as construction workers carry out dual roles. The main reason for choosing a job as a construction worker was due to family economic pressures. Apart from economic reasons, there are other reasons that support women in working as construction workers, including low education, wanting to send their children to school, limited skills, polygamous husbands and husbands' own income.